Dynamics of Beta-Glucosidase Zm-p60.1 Ectopic Expression During Transgenic Pollen Development: A Histochemical Approach - Dubová, J; Mlejnek, P; Brzobohatý, Břetislav (General physiology and biophysics, 1999)
Zm-p60.1 is maize cDNA coding cytokinin-glucoside specific beta-glucosidase. Indigogenic method was used for histochemical localization of Zm-p60.1 beta-glucosidase activity in various developmental stages of transgenic tobacco anthers. Expression of Zm-p60.1 cDNA in T7 tobacco plants is controlled by the CaMV 35S promoter. Another type of tobacco transformant expresses Zm-p60.1 under the control of LAT 52 promoter. Histochemical detection has proved different patterns of beta-glucosidase activity during tobacco pollen development in these two types of transformants. Zm-p60.1 beta-glucosidase activity had not direct influence on pollen germinability.
Keywords: DNA Primers; kukuřice setá; DNA primery; jedovaté rostliny; Pollen; Nicotiana; messenger RNA; pyl; RNA, Plant; geneticky modifikované rostliny; beta-Glucosidase; RNA rostlin; sekvence nukleotidů; transformace genetická; Plants, Genetically Modified; Transformation, Genetic; Plants, Toxic; tabák; Gene Expression; Zea mays; RNA, Messenger; beta-glukosidasa; exprese genu; Base Sequence